2019
DOI: 10.1186/s12872-019-01296-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alterations in serum immunoglobulin concentrations in components of metabolic syndrome, obesity, diabetes, and dyslipidemia

Abstract: PurposeSerum immunoglobulins (Igs) play a critical role in modulating the immune response by neutralizing pathogens, although little is known about the effect of Igs in development of atherosclerotic cardiovascular disease (ASCVD). Elevated serum Immunoglobulin A (IgA) concentrations have been identified in previous studies in populations with obesity and hypertriglyceridemia, whereas variable concentrations of Immunoglobulin M (IgM) have been observed in the setting of dyslipidemia.MethodsIn this cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The elevation of globulin in the case group (Figure 1) suggests chronic low-grade inflammation and elevated serum levels of systemic inflammatory markers commonly found in obesity-related insulin resistance, type 2 diabetes, and metabolic syndrome [29,30]. This inflammation is suspected to be because of hypercholesterolemia which was found in this study to be significantly positively correlated with (Table 8).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The elevation of globulin in the case group (Figure 1) suggests chronic low-grade inflammation and elevated serum levels of systemic inflammatory markers commonly found in obesity-related insulin resistance, type 2 diabetes, and metabolic syndrome [29,30]. This inflammation is suspected to be because of hypercholesterolemia which was found in this study to be significantly positively correlated with (Table 8).…”
Section: Discussionsupporting
confidence: 58%
“…Like in ALT, serum elevation of AST among the case group (Figure 1) is also an indication of liver dysfunction, however, the elevation may also be due to extrahepatic disorders, e.g., celiac sprue, muscle disorders, thyroid disorders, and haemolysis [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study noted decreased IgG and immunoglobin M levels independently related to the prevalence of adult type 2 diabetes ( 23 ). In contrast another cross-sectional study was unable to identify an association with overall serum immunoglobin levels in individuals with diabetes but found that dyslipidemia was associated with a lower serum IgG concentration ( 24 ). The relationship between serum levels of immunoglobulins and MetS were further explored in the TCLSIH cohort study ( 25 ) and demonstrated that decreased IgG and increased immunoglobin A were independently related to a higher prevalence of MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly in our study, deceased people suffering from other clinical manifestations also showed lower neutralizing and other measurable antibody release when compared to the participants who have underlying diseases with moderate manifestations [ 30 ]. Further, several studies have showed that cardiac vascular dysfunctions and metabolic diseases could cause humoral immunity disturbance and affect the production of antibodies [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%